2017
DOI: 10.1007/s00223-017-0373-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone Loss in Rheumatoid Arthritis: Basic Mechanisms and Clinical Implications

Abstract: Patients with rheumatoid arthritis (RA) have historically developed progressive damage of articular bone and cartilage, which correlates with disability over time. In addition, these patients are prone to periarticular and systemic bone loss, carrying additional morbidity. In contrast to what is seen in many other rheumatic diseases, the impact of inflammation on bone in RA is uniquely destructive. Loss of articular bone (erosions) and periarticular bone (demineralization) is a result of excessive bone resorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 145 publications
0
77
0
Order By: Relevance
“…Bone homeostasis is maintained balancing boneresorbing osteoclast and bone-forming osteoblast activity, alteration of this balance causes bone loss, that is not recov-ered by new bone formation. In fact, in inflammation, disease-like RA bone erosion results from excessive bone resorption and markedly limited bone formation [38]. We observed typical morphological markers of new bone formation on incus by CHO, but this phenomenon probably happens at a slower rate than bone resorption, so that bone loss is not compensed.…”
Section: Observation Of Newmentioning
confidence: 71%
“…Bone homeostasis is maintained balancing boneresorbing osteoclast and bone-forming osteoblast activity, alteration of this balance causes bone loss, that is not recov-ered by new bone formation. In fact, in inflammation, disease-like RA bone erosion results from excessive bone resorption and markedly limited bone formation [38]. We observed typical morphological markers of new bone formation on incus by CHO, but this phenomenon probably happens at a slower rate than bone resorption, so that bone loss is not compensed.…”
Section: Observation Of Newmentioning
confidence: 71%
“…Cytokines, such as tumor necrosis factor, interleukin‐1β (IL‐1β), IL‐6, and IL‐17, are effective triggers of bone resorption and some are now targeted in the clinic with inhibitors showing an effect on bone destruction . These cytokines induce osteoclast differentiation directly or indirectly by increasing the expression of RANKL, which leads to an increase in osteoclast differentiation and bone resorption activity, and subsequent bone erosion . Joint damage can be found in patients who have had RA for only a short time, and studies have shown enhanced levels of bone metabolism markers in RA patients with preclinical disease, which suggests that bone erosion might happen before the onset of clinical inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Color figure can be viewed in the online issue, which is available at http://onlinelibrary.wiley.com/doi/10.1002/art.40868/abstract. in osteoclast differentiation and bone resorption activity, and subsequent bone erosion (32)(33)(34). Joint damage can be found in patients who have had RA for only a short time, and studies have shown enhanced levels of bone metabolism markers in RA patients with preclinical disease, which suggests that bone erosion might happen before the onset of clinical inflammation (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune disease, characterized by immune cell‐mediated destruction of the joints. Hyper‐reactive T and B lymphocytes are key cells in the destructive process by producing inflammatory cytokines and autoantibodies . The protein tyrosine phosphatase non‐receptor type 22 gene ( PTPN22 ) encodes the lymphoid protein tyrosine phosphatase LYP, which is expressed exclusively in hematopoietic cells, including T and B cells .…”
Section: Introductionmentioning
confidence: 99%
“…Hyper-reactive T and B lymphocytes are key cells in the destructive process by producing inflammatory cytokines and autoantibodies. 1 The protein tyrosine phosphatase non-receptor type 22 gene (PTPN22) encodes the lymphoid protein tyrosine phosphatase LYP, which is expressed exclusively in hematopoietic cells, including T and B cells. 2 LYP is a potent negative regulator of T and B lymphocyte activation by modulating T-cell receptor (TCR) and B-cell receptor (BCR) signaling.…”
Section: Introductionmentioning
confidence: 99%